Convenient Synthesis of Fluorescent Chromeno[4,3-d]pyrimidines from Electron-Deficient 3-Vinylchromones - Chernov, Nikita M.; Shutov, Roman V.; Potapova, Anastasia E.; Yakovlev, Igor P. (Synthesis, 2020)
We report an easy and powerful approach to the synthesis of novel chromeno[4,3-d]pyrimidine-5-acetic acids through ANRORC reaction of electron-deficient 3-vinylchromones and 1,3-N,N-binucleophiles. The reaction proceeds under mild conditions (EtOH, rt) and is applicable to a wide range of substrates. The described compounds show fluorescence in the violet-blue range (390–460 nm) with Stokes shift of 40–80 nm and moderate quantum yield (0.15–0.20). As the electron-withdrawing group is conserved in the form of an acetic acid fragment, these compounds may readily be functionalized or conjugated to a required substrate for (bio)analytical purposes.
Keywords: chromeno[4,3-d]pyrimidine; pyrimidine; chromone; amidine; ANRORC; fluorescence